2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24810
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Electronics to First-year Engineering Students

Abstract: Introduction:There is no doubt that engineers significantly contribute to the growth of any nation's economy. However, the rate of engineering innovations and initiatives poses a great challenge to the United States (US) due to the high attrition rates observed in engineering programs in the US.Attrition is recognized as a significant problem in engineering education; engineering programs are reporting graduation rates in the range of 40-60%.1-7 Students seem to experience a loss of interest and lack of motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Based upon research, it is known that high attrition rates in engineering programs are partly due to the programs being theory-focused and lacking a practical, hands-on component that enables students to understand the visualize the relevance of their classroom knowledge 4,5,6,7 . Additionally, the introduction of new, state-of-the-art technology into the learning process can also enhance the educational experience for students.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon research, it is known that high attrition rates in engineering programs are partly due to the programs being theory-focused and lacking a practical, hands-on component that enables students to understand the visualize the relevance of their classroom knowledge 4,5,6,7 . Additionally, the introduction of new, state-of-the-art technology into the learning process can also enhance the educational experience for students.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that students are losing interest and motivation to continue in engineering within the first two years of college, an important reason for students leaving engineering programs [1] . Therefore, maintaining the interest in engineering for first-year engineering (FYE) students is critical to promote student retention in engineering.…”
Section: Introductionmentioning
confidence: 99%